Advancing climate resilience in agriculture via climate information services in Myanmar - Barbon, Wilson John; Khaung, Ye (International Institute of Rural Reconstruction, 2022)
This document is developed to inform key agricultural stakeholders working in Myanmar about the importance of climate information in enhancing the resilience of the agriculture sector to the impact of climate change. The report is divided into three main parts: i) an overview of climate risks and their impact on Myanmar agriculture; ii) an existing climate information service based on main climate services pillars from generation, translation, dissemination, and use; and iii) areas for further investment and support for scaling out the activities in the future.